Energy of the Photosubstitutionally Reactive Excited State of Pentaammine(pyridine)ruthenium(II) - Carlos, Rose M. [UNESP]; Neumann, Miguel G.; Tfouni, Ella (American Chemical Society (ACS), 1996)
The photosensitized aquation of pentaammine(pyridine)ruthenium(II) by several dyes has been studied under conditions where only the sensitizers absorb light. The ratio of the quantum yields for ammine and pyridine substitution was the same as that for direct photoaquation. Sensitization was effective with singlet sensitizers Rhodamine-B (17 452 cm -1) and Safranine-T (17 690 cm -1), as well as the triplet sensitizer biacetyl (19 000 cm -1), but no reaction was observed with Neutral-Red (16 900 cm -1). The results indicate that the excited state precursor of the observed photosubstitution in the complex lies in the energy range between 17 000 and 17 700 cm -1.